Aged Garlic Extract Ameliorates Chronic Restraint Stress-Induced Depressive and Anxiety-like Behavior in Mice: In Vivo and In Silico Approaches (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Stress is a common factor that can lead to various health issues, including depression and anxiety. Aged garlic extract (AGE) has been suggested to have potential therapeutic benefits, including antidepressant and anxiolyticlike effects. This study aimed to investigate the effects of AGE on depressive and anxiety-like behavior induced by chronic restraint stress in mice using both in vivo and in silico approaches. In vivo experiments involved subjecting mice to chronic restraint stress to induce depressive-like behavior. The mice were then treated with AGE, and their behavioral outcomes were assessed using the forced swim test and tail suspension test, open field test, and elevated maze plus. Additionally, an in silico analysis was conducted to explore the potential mechanisms of action of AGE compounds, focusing on their interactions with the monoanime oxidase-A (MAO-A) enzyme. The in vivo experiments demonstrated that the administration of aged garlic extract significantly ameliorated behavioral deficits in mice subjected to chronic restraint stress. Specifically, AGE treatment led to reduced (p